THE IMPORTANT ROLE OF MOSQUE CLERIC OF CHINESE DESCENT IN SPREADING ISLAM AT CIREBON’S LAUTZE MOSQUE ENVIRONMENT TOWARD ETHNIC CHINESE - Muhammad Yusuf; Rafyon Sani; Syakina; Jerry Heikal (Jurnal Media Akademik (JMA), 2024)
Cirebon's Lautze 3 Mosque, standing firmly in the middle of Cirebon's Chinatown, West Java, is a silent witness to the inspiring story of Islamic preaching among ethnic Chinese. Founded in 2022, this mosque has become a spiritual oasis for the Chinese Muslim community in the area, led by mosque administrators who have a unique background: ethnic Chinese converts. Their story is clear proof that Islamic preaching has no limits. Their experience as converts allowed them to bridge cultural gaps and build trust with non-Muslim Chinese communities. This da'wah approach that is sensitive to culture and community needs is the key to their success in spreading Islam in Cirebon's Chinatown environment. More than just a place of worship, the Lautze 3 Cirebon Mosque has become a community and missionary center for Chinese Muslims in Cirebon. His presence is a symbol of tolerance and unity amidst cultural and ethnic diversity. The inspiring story of the mosque administrators is a reminder for all of us that Islamic da'wah must be carried out with love, understanding and respect for local culture and traditions. Mosque administrators can be more effective in developing da'wah strategies that benefit both parties, as well as building harmonious and mutually beneficial relationships between the Muslim and Chinese communities in Chinatown.